Students Viewed on Digital Platforms for Online Learning During Covid-19 Pandemic - Muthi, Amiruddin; Sugiarto, Sugiarto; Sarkadi, Sarkadi (Jurnal Paedagogy, 2023)
The study aims to obtain the digital platforms students use for online learning, perceptions, and problems using digital platforms at Madrasah Tsanawiyah during the Covid-19 pandemic. This research used qualitative research through a case study. The participants in this study were 100 students at MTs Miftahul Huda who were taken randomly from grade one to grade three. Documents, observations, and a questionnaire were used to collect data. Data analysis entailed gathering information, reducing it, presenting it, and drawing conclusions. The findings showed that students preferred offline learning to online learning. At the same time, the preferred online applications are zoom and WA. The obstacles faced were the internet network, the ability to provide internet quota, and psychological challenges related to being active in class. So, various digital platforms only sometimes provide comfort and suit the needs of students in online classes. These findings provide an understanding from the student’s perspective that digital platforms must be adapted to the learning environment at home, family conditions, and the readiness of the teacher or students themselves.